Endocrine and glycolipid metabolism characteristics of diminished ovarian reserve in Chinese women with polycystic ovary syndrome. Issue 3 (March 2020) - Wang, Chaojun; Di, Wen; Gu, Zhuowei
Objective: This study was performed to evaluate the endocrine and glycolipid metabolism characteristics of diminished ovarian reserve (DOR) in Chinese patients with polycystic ovary syndrome (PCOS). Methods: In total, 1179 patients with PCOS and 70 healthy women who presented to the Department of Gynecological Endocrinology in Ren Ji Hospital from June 2015 and June 2019 were enrolled in this study. Parameters of endocrine and glycolipid metabolism were measured. The differences in indices among the control group, simple PCOS group, and PCOS with DOR group were analyzed. Results: The prevalence of DOR in Chinese women with PCOS was 20.8%. The body mass index and waist/hip ratio were significantly higher in the simple PCOS group than in the PCOS with DOR group. There were significant differences in the concentrations of luteinizing hormone, follicle-stimulating hormone, estradiol, testosterone, and androstenedione among the three groups. The fasting serum insulin concentration and homeostatic model assessment of insulin resistance were significantly higher in the simple PCOS group than in the PCOS with DOR group. Conclusions: The endocrine and glycolipid metabolism characteristics were different between the simple PCOS group and PCOS with DOR group.